Hidden History : African American Cemeteries in Central Virginia - Rainville, Lynn (Book collections on Project MUSE., 2014)
"In Hidden History, Lynn Rainville travels through the forgotten African American cemeteries of central Virginia to recover information crucial to the stories of the black families who lived and worked there for over two hundred years. The subjects of Rainville's research are not statesmen or plantation elites; they are hidden residents, people who are typically underrepresented in historical research but whose stories are essential for a complete understanding of our national past. Rainville studied above-ground funerary remains in over 150 historic African American cemeteries to provide an overview of mortuary and funerary practices from the late eighteenth century to the end of the twentieth. Combining historical, anthropological, and archaeological perspectives, she analyzes documents--such as wills, obituaries, and letters--as well as gravestones and graveside offerings. Rainville's findings shed light on family genealogies, the rise and fall of segregation, and attitudes toward religion and death. As many of these cemeteries are either endangered or already destroyed, the book includes a discussion on the challenges of preservation and how the reader may visit, and help preserve, these valuable cultural assets."--Publisher's Web site